1984
DOI: 10.2134/jeq1984.00472425001300020012x
|View full text |Cite
|
Sign up to set email alerts
|

Drip Irrigation of Cotton with Treated Municipal Effluents: II. Nutrient Availability in Soil

Abstract: The suitability of sewage effluent for drip irrigation of cotton (Gossypium hirsutum) growing on a deep calcareous clay soil (Typic Chromoxererts) was studied during three seasons. Secondary effluent was compared with freshwater at three application rates, the average of which for the three seasons were: low (350 mm yr−1), standard (440 mm yr−1), and high (515 mm yr−1). Fertilizer was applied with the fresh water in order to deliver amounts of nutrients (average for the 3 years) equivalent to those in the effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
1
21
0
4
Order By: Relevance
“…The response of plants and soils to municipal treated effluent is dependent on the quality of the applied effluent and nature and efficiency of the wastewater treatment, with generally higher treated water resulting in the best growth and yields (Basiouny, 1984). Recently, wastewater has been used to increase yield and improve quality of grain crops (Al-Jaloud et al, 1993;Day & Tucker, 1977;Day et al, 1975;Karlen et al, 1976;Morvedt & Giovdane, 1975;Nguy, 1974), cotton Feigin et al, 1984), forage (Bole & Bell, 1978) and vegetable crops (Basiouny, 1984;Kirkham, 1986;Neilsen et al, 1989Neilsen et al, a, b, c, 1991Ramos et al, 1989). Reclaimed water has been successfully used to irrigate many fruit crops; apples (Nielsen et al, 1989a), cherries (Neilsen et al, 1991), grapes (Neilsen et al, 1989a), peaches (Basiouny, 1984) and citrus (Esteller et al, 1994;Kale & Bal, 1987;Koo & Zekri, 1989;Morgan et al, 2008;Omran et al, 1988;Wheaton & Parsons, 1993;Zekri & Koo, 1990).…”
Section: Wastewater Reuse: the General Casementioning
confidence: 99%
See 4 more Smart Citations
“…The response of plants and soils to municipal treated effluent is dependent on the quality of the applied effluent and nature and efficiency of the wastewater treatment, with generally higher treated water resulting in the best growth and yields (Basiouny, 1984). Recently, wastewater has been used to increase yield and improve quality of grain crops (Al-Jaloud et al, 1993;Day & Tucker, 1977;Day et al, 1975;Karlen et al, 1976;Morvedt & Giovdane, 1975;Nguy, 1974), cotton Feigin et al, 1984), forage (Bole & Bell, 1978) and vegetable crops (Basiouny, 1984;Kirkham, 1986;Neilsen et al, 1989Neilsen et al, a, b, c, 1991Ramos et al, 1989). Reclaimed water has been successfully used to irrigate many fruit crops; apples (Nielsen et al, 1989a), cherries (Neilsen et al, 1991), grapes (Neilsen et al, 1989a), peaches (Basiouny, 1984) and citrus (Esteller et al, 1994;Kale & Bal, 1987;Koo & Zekri, 1989;Morgan et al, 2008;Omran et al, 1988;Wheaton & Parsons, 1993;Zekri & Koo, 1990).…”
Section: Wastewater Reuse: the General Casementioning
confidence: 99%
“…In the same study, leaf N contents were slightly lower in plants irrigated with groundwater than wastewater (Parsons et al, 2001b). It was concluded that this was due to elevated levels of organic matter found in wastewater which provided additional N. Higher leaf N was also found in treated wastewater irrigated sweet-cherry (Neilsen et al,1991), apples (Neilsen et al, 1989c), cotton (Feigin et al, 1984) and peach trees (Basiouny, 1984). No significant differences in leaf P contents were found between plants irrigated with either groundwater or wastewater, in spite of wastewater supplying a higher soil P load.…”
Section: Wastewater Irrigation Of Florida Citrus: a Case Studymentioning
confidence: 99%
See 3 more Smart Citations